Post-viral idiopathic purpura fulminans is associated with inherited thrombophilia and anti-cardiolipin antibodies - A. Theron; A. Theron; A. Theron; S. Ayadi; E. Boissier; O. Dautremay; O. Dautremay; J.-F. Schved; N. Sirvent; I. Diaz; G. Captier; G. Captier; et al. (Frontiers Media S.A., 2023)
IntroductionIdiopathic purpura fulminans (IPF) is a rare and severe coagulation disorder, associated with transient anti-protein S (anti-PS) antibodies in the context of post-viral infection such as varicella. Anti-protein S antibodies are frequently found in the context of varicella, in contrast with the rarity of IPF. Other factors such as anti-phospholipid antibodies (APL) and inherited thrombophilia may be associated with severe vascular complication.MethodThis is an ancillary study of a French multicenter retrospective series and systematic review of literature. We analyzed patients who were tested for inherited thrombophilia, namely antithrombin, protein C, protein S deficiency; prothrombin gene G20210A polymorphism (FII:G20210A),Factor V R506Q polymorphism (FV:R506Q); and/or for APL (lupus anticoagulant (LA), anti-cardiolipin antibodies (ACL), or anti-beta 2-GPI antibodies (Aβ2GP1).ResultsAmong the 25 patients tested for inherited thrombophilia, 7 (28%) had positive results. Three had FV R506Q, two FII:G20210A, one compound heterozygote FV:R506Q associated to FII:G20210A, and one protein C deficiency. APL testing was performed in 32 patients. It was positive in 19 patients (59%): 17 ACL (53%), 5 LA (16%), 4 Aβ2GP1 (13%). The risk of severe complications was not associated with presence of inherited thrombophilia or APL presence, with RR: 0.8 [95% CI: 0.37-1.71], p = 1 and RR: 0.7 [95% CI: 0.33-1.51], p = 0.39, respectively. We found a high prevalence of inherited thrombophilia or APL in a population of patients with IPF. However, we do not find an association with the occurrence of severe vascular complications or venous thromboembolism.